A stabilizing factor?–Video gaming among elite athletes during the first lockdown of the COVID-19 pandemic - Breckwoldt, Tabea; Fröhlich, Stefan; Iff, Samuel; Bitar, Raoul; Spörri, Jörg; Scherr, Johannes; Seifritz, Erich; Quednow, Boris B.; Claussen, Malte Christian (Frontiers in Psychology, 2022)
Objectives: Little is known about the extent of video gaming among elite athletes, specifically under stressful conditions like those induced by the current COVID-19 pandemic. The aim of this study was to evaluate the intensity and extent of video gaming in the context of the COVID-19 pandemic, during which the usual daily routine of many athletes was disrupted. Methods: Overall, 203 elite athletes from Switzerland who participated in Olympic sports or in ’International Olympic Committee’-approved disciplines were interviewed using an online questionnaire. They were questioned on their video game consumption during the first Swiss lockdown during the COVID-19 pandemic as well as on their athletic performance and economic circumstances. Additionally, mental and physical health were assessed by standardized questionnaires. From this questionnaire data, predictors of gaming time were evaluated using multivariable analysis. Results: Before the lockdown, 21% of the participating athletes played video games regularly. The average playing time was 15.8 hours per month within the gamer group. During the first lockdown, 29% of athletes reported gaming regularly, and within the gamer group the average gaming time increased significantly, by 164%. The mental health burden showed significant differences between gamers and non-gamers regarding existential fears during the lockdown, the ability to cope with governmental measures due to COVID-19 and total sleeping time. However, there was no statistical difference in respect to standardized scales for depressive symptoms, sleep behavior, and anxiety. Higher video gaming time during the lockdown was significantly associated with male gender and previous gaming before the COVID-19 lockdown. Conclusion: Video gaming time increased significantly during the first lockdown. Whether video gaming among elite athletes hereby functions as an effective coping behavior remains to be shown and requires more research.